2011
DOI: 10.1016/j.chb.2011.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The lies we tell and what they say about us: Using behavioural characteristics to explain Facebook activity

Abstract: The Open University's repository of research publications and other research outputs The lies we tell and what they say about us: using behavioural characteristics to explain Facebook activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 31 publications
2
47
0
Order By: Relevance
“…That is, those who prefer social activities but lack communication competence were more likely to use Twitter in a more inward-oriented manner that does not actively engage other social beings than were their socially competent counterparts. Thus far, some researchers have contrasted interpersonal SNS use (i.e., communication) with more ego-centric SNS use (i.e., broadcasting) (Underwood, Kerlin, & Farrington-Flint, 2011), each of which is driven by social interaction and impression management motivations, respectively. Such conceptual distinction is also echoed in the dual-factor model of Facebook use, which proposes the need for self-presentation and the need to belong as the two ''basic social needs'' prompting Facebook use (Nadkarni & Hofmann, 2012, p. 245).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…That is, those who prefer social activities but lack communication competence were more likely to use Twitter in a more inward-oriented manner that does not actively engage other social beings than were their socially competent counterparts. Thus far, some researchers have contrasted interpersonal SNS use (i.e., communication) with more ego-centric SNS use (i.e., broadcasting) (Underwood, Kerlin, & Farrington-Flint, 2011), each of which is driven by social interaction and impression management motivations, respectively. Such conceptual distinction is also echoed in the dual-factor model of Facebook use, which proposes the need for self-presentation and the need to belong as the two ''basic social needs'' prompting Facebook use (Nadkarni & Hofmann, 2012, p. 245).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…In general, users of social networks are extroverts who are willing to risk more, and men outnumber women (Underwood, Kerlin, & Farrington-Flint, 2011). Ross et al (2009) suggest that Facebookers' personality traits are correlated with visit frequency and time of use.…”
mentioning
confidence: 98%
“…Surpassing the predominantly text-based methods of early computer-mediated communication, these sites afford users the ability to share a vast array of information in multimedia-rich environments. For the millions of global users who regularly engage with these sites (Ofcom, 2014), it has been suggested that they provide an online equivalent to faceto-face communication contexts (Underwood, Kerlin & Farrington-Flint, 2011), and in doing so carry the potential of delivering a range of social and psychological benefits (Burke & Kraut, 2014;Ellison, Steinfield & Lampe, 2007;Valkenburg, Peter & Schouten, 2006). At the same time, an area of mounting academic interest is addressing the potential associated risks and vulnerabilities of using SNS to interact and communicate with our social connections (Debatin, Lovejoy, Horn, & Hughes, 2009;Fogel & Nehmad, 2009;Wilcox & Stephen, 2012).…”
Section: Online Vulnerability and Social Network Sitesmentioning
confidence: 99%